An Optimal Secondary Multi-Bus Voltage and Reactive Power Sharing Control Based on Non-Iterative Decoupled Linearized Power Flow for Islanded Microgrids - Wong, Yi Chyn Cassandra; Lim, Chee Shen; Goh, Hui Hwang; Cruden, Andrew; Rotaru, Mihai Dragos; Kong, Xin (IEEE access, 2021)
The subject of optimal secondary control of power-electronic-interfaced distributed energy resources (DERs) in droop-controlled microgrids has garnered significant research attention in recent years. While the feasibility of optimal secondary control based on non-linear power flow has been proven, the power flow algorithm is essentially iterative in nature. This work proposes an optimal secondary control with non-iterative power flow to regulate multi-bus voltages and DERs' reactive powers. The control scheme incorporates a modified Decoupled Linearized Power Flow that is known to be superior in terms of reactive power and bus voltage magnitude estimation, as compared to classical DC power flow, into a constrained quadratic programming. Q-V droop is integrated into the linear power flow in place of the slack bus. The proposed optimal scheme is provably accurate for maintaining reactive power sharing while regulating multiple load-bus voltages. The additional degrees of freedom enabled by the weighting factors significantly improve the control flexibility of the secondary controller. The allowable bus voltages and DER kVar capacity limits have also been considered by the control algorithm. The work is proven through an accurate co-simulation study comprising an 18-bus network and a full primary control models in PowerFactory , interfaced through industrial communication tool MatrikonOPC .